EVALUATION OF EFFECTS OF DIFFERENT COMBINATIONS OF SELECTED SEDATIVES ON THE HEMATOLOGICAL PROFILE OF STANDING SEDATED HORSES - H. B. Rashid; M. S. Khan; M. Chaudhry; M. A. Khan; M. Ashraf (Journal of Animal and Plant Sciences, 2017)
Alpha-2 agonists induce changes in the hemogram in equines. The aim of the present study was to examine the magnitude of changes in the selected blood parameters produced by various α-2- agonists combinations. For this purpose, 25 horses were the animals of study during different clinical examinations and minor surgical interventions in standing sedation. Blood samples were collected from the jugular venipuncture of horses before sedation, 15 mins., 30 mins., and 60 mins., after drug administration.The blood parameters evaluated were Packed cell volume (PCV), Haemoglobin concentration (Hb), Red blood cells (RBC), Total leukocytes count (TLC), and Differential leucocytes count (DLC) (neutrophils, eosinophils and monocytes). Analysis of variance (1-way ANOVA) were performed with p<0.05. Hb, PCV, TLC and DLC declined gradually in all groups post drug administration. Pre-sedation values for all parameters were significantly different from post-sedation values at 15, 30, and 60 minutes. There was no significant effect of drug groups on Hb, neutrophil and eosinophil values. Group A (Acepromazine + Detomidine combination) produced significant decrease in PCV values compared with group C (Acepromazine + Ketamine) and group D (Acepromazine + Detomidine + Ketamine). RBC values of group B (Detomidine + Ketamine) showed significant difference compared with group C, D, & E (Acepromazine + Xylazine + Ketamine). TLC and monocyte values of group B were significantly different from D & E groups. It was concluded that drug combination with acepromazine, detomidine, xylazine and ketamine cause minimal hematological side effects. Therefore, these drugs could be safely used for inducing standing sedation in horses.
Keywords: Horses; Standing sedation; Acepromazine; Detomidine; Ketamine; Xylazine; Hematology